Transcriptional profiling of mycobacterial antigen-induced responses in infants vaccinated with BCG at birth - Fletcher, H; Keyser, A; Bowmaker, M; Sayles, P; Kaplan, G; Hussey, G; Hill, A; Hanekom, W (BioMed Central, 2009)
Background: Novel tuberculosis (TB) vaccines recently tested in humans have been designed to boost immunity induced by the current vaccine, Mycobacterium bovis Bacille Calmette-Guérin (BCG). Because BCG vaccination is used extensively in infants, this population group is likely to be the first in which efficacy trials of new vaccines will be conducted. However, our understanding of the complexity of immunity to BCG in infants is inadequate, making interpretation of vaccine-induced immune responses difficult. Methods: To better understand BCG-induced immunity, we performed gene expression profiling in five 10-week old infants routinely vaccinated with BCG at birth. RNA was extracted from 12 hour BCG-stimulated or purified protein derivative of tuberculin (PPD)-stimulated PBMC, isolated from neonatal blood collected 10 weeks after vaccination. RNA was hybridised to the Sentrix® HumanRef-8 Expression BeadChip (Illumina) to measure expression of >16,000 genes. Results: We found that ex vivo stimulation of PBMC with PPD and BCG induced largely similar gene expression profiles, except that BCG induced greater macrophage activation. The peroxisome proliferator-activated receptor (PPAR) signaling pathway, including PPAR-γ, involved in activation of the alternative, anti-inflammatory macrophage response was down-regulated following stimulation with both antigens. In contrast, up-regulation of genes associated with the classic, pro-inflammatory macrophage response was noted. Further analysis revealed a decrease in the expression of cell adhesion molecules (CAMs), including integrin alpha M (ITGAM), which is known to be important for entry of mycobacteria into the macrophage. Interestingly, more leukocyte genes were down-regulated than up-regulated. Conclusion: Our results suggest that a combination of suppressed and up-regulated genes may be key in determining development of protective immunity to TB induced by vaccination with BCG.